Transporter gene acquisition and innovation in the evolution of Microsporidia intracellular parasites - P. Dean (Nature Portfolio, 2018)
Microsporidia are obligate intracellular parasites that infect both humans and animals. Here, Dean et al. perform ancient gene reconstruction and functional assays to investigate the evolution and functional diversification of nucleotide transporters which are key to the parasite's intracellular lifestyle.